Lenzimycins A and B, Metabolites With Antibacterial Properties From Brevibacillus sp. Associated With the Dung Beetle Onthophagus lenzii - An, Joon Soo; Hong, Seong-Heon; Somers, Elisabeth; Lee, Jayho; Kim, Byung-Yong; Woo, Donghee; Kim, Suk Won; Hong, Hee-Jeon; Jo, Shin-Il; Shin, Jongheon; Oh, Ki-Bong; Oh, Dong-Chan (Frontiers in Microbiology, 2020)
Symbiotic microorganisms associated with insects can produce a wide array of metabolic products, which provide an opportunity for the discovery of useful natural products. Selective isolation of bacterial strains associated with the dung beetle, Onthophagus lenzii, identified two strains, of which the antibiotic-producing Brevibacillus sp. PTH23 inhibited the growth of Bacillus sp. CCARM 9248, which is most closely related to the well-known entomopathogen, B. thuringiensis. A comprehensive chemical investigation based on antibiotic activity discovered two new antibiotics, named lenzimycins A and B (1-2), which inhibited growth of Bacillus sp. CCARM 9248. The 1H and 13C NMR, MS, MS/MS, and IR analyses elucidated the structures of 1 and 2, which comprised a novel combination of fatty acid (12-methyltetradecanoic acid), glycerol, sulfate, and N-methyl ethanolamine. Furthermore, the acid hydrolysis of 1 revealed the absolute configuration of 12-methyltetradecanoic acid as 12S by comparing its optical rotation value with authentic (R)- and (S)-12-methyltetradecanoic acid. In addition to inhibition of Bacillus sp. CCARM 9248, lenzimycins A and B were found to inhibit the growth of some human pathogenic bacteria, including Enterococcus faecium and certain strains of E. faecalis. Furthermore, the present study elucidated that lenzimycins A and B activated a reporter system designed to detect the bacterial cell envelope stress, thereby indicating an activity against the integrity of the bacterial cell wall.